Insulin and aging – a disappointing relationship - Kolb, Hubert; Kempf, Kerstin; Martin, Stephan (Frontiers in Endocrinology, 2023)
Experimental studies in animal models of aging such as nematodes, fruit flies or mice have observed that decreased levels of insulin or insulin signaling promotes longevity. In humans, hyperinsulinemia and concomitant insulin resistance are associated with an elevated risk of age-related diseases suggestive of a shortened healthspan. Age-related disorders include neurodegenerative diseases, hypertension, cardiovascular disease, and type 2 diabetes. High ambient insulin concentrations promote increased lipogenesis and fat storage, heightened protein synthesis and accumulation of nonfunctional polypeptides due to limited turnover capacity. Moreover, there is impaired autophagy activity, and less endothelial NO synthase activity. These changes are associated with mitochondrial dysfunction and oxidative stress. The cellular stress induced by anabolic activity of insulin initiates an adaptive response aiming at maintaining homeostasis, characterized by activation of the transcription factor Nrf2, of AMP activated kinase, and an unfolded protein response. This protective response is more potent in the long-lived human species than in short-lived models of aging research resulting in a stronger pro-aging impact of insulin in nematodes and fruit flies. In humans, resistance to insulin-induced cell stress decreases with age, because of an increase of insulin and insulin resistance levels but less Nrf2 activation. These detrimental changes might be contained by adopting a lifestyle that promotes low insulin/insulin resistance levels and enhances an adaptive response to cellular stress, as observed with dietary restriction or exercise.